Upaya Guru Menanamkan Sikap Sopan Santun Anak Di TK Kemala Bhayangkari 1 Palembang - ., Lindarsih; ., Retno Wulandari; ., Fahmi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The research I did was descriptive qualitative research.the purposeof the research that I didwas to describe the difficulties faced by eachers in an effort to instill good manners in children at kindergarten kemala bhayangkari 1 palembang and to explain solutions in overcoming obstacles that occurred,and to describe efforts to instill good manners kindergarten kemala bhayangkari to shape the polite behavior of children in calss A.this research was carried out in kindergarten kemala bhayangkari 1 palembang.the data collection echnique I did was collect data used by observation ,interviews,documentation of the results of this research.good manners for children to give understanding to children always respect older people give a warning to children who speak impolitely to people who are older than him give examples of polite behavior to children before lessons begin the difficulties faced by the teacher in shaping the child’s character lack self –confidence in children,the solution applied by classroom teachers,namely teaching with love and special attentions as a teacher,naturally becomes a good example for children.